Incidence of new hepatitis C virus infection is still increasing in French MSM living with HIV. (15th May 2018) - Pradat, Pierre; Huleux, Thomas; Raffi, François; Delobel, Pierre; Valantin, Marc-Antoine; Poizot-Martin, Isabelle; Pugliese, Pascal; Reynes, Jacques; Rey, David; Hoen, Bruno; Cabie, André; Bani-Sadr, Firouzé; et al.
Abstract : Objective: High hepatitis C virus (HCV) treatment uptake combined with effective direct-acting antiviral-based regimens resulted in a dramatic decline of HCV infection in French people living with HIV (PLWH). We assessed the yearly incidence of new HCV infection in PLWH enrolled in the large French Dat'AIDS cohort from 2012 to 2016 with a specific focus on MSM. Methods: The incidence of new HCV infection was determined yearly in HCV-negative PLWH with serological follow-up during 2012–2016. The incidence of HCV reinfection was determined in patients who were cured of a previous infection. Results: Among 40 714 PLWH, HCV status was available in 38 217 (94%). A total of 5557 PLWH (15%) were HCV infected at first time-point, 82% of whom were cured of HCV by the end of 2016. Among 21 519 HCV-negative PLWH with serological follow-up (63 449 patient-years), 219 first HCV infections occurred (MSM: 188, others: 31). Similarly, among 3406 patients who were cured of a previous infection (10 602 patient-years), 73 reinfections occurred (MSM: 51, others: 22). From 2012 to 2016, the incidence of a first infection in MSM rose from 0.5 to 0.92% patient-years, whereas the incidence or reinfection remained stable (2.52–2.90% patient-years). Conclusion: Despite a high HCV treatment uptake and cure rate, the incidence of first HCV infection regularly increased in French HIV-positive MSM between 2012 and 2016. The incidence of reinfection fluctuated but remained constantly higher than the incidence of first infection, suggesting that a subgroup of MSM pursued high-risk practices following cure of a first infection. Abstract : Supplemental Digital Content is available in the text